IMPLEMENENTASI SISTEM INFORMASI PENGELOLAAN INVENTORY FIXED ASSET PADA PT. ARK LOGISTICS DAN TRANSPORT - Hasan, Haryani (www.bsi.ac.id, 2017)
Fixed Assets, as known as tangible assets and typically lose value over time (except land) and also be defined as an asset not directly sold to a firm's consumers/end-users. In a logistics & transport industry, these fixed assets include items or tools that help obtain and maintain business operations. For examples table, chair, computer PC. They have an important role which is support the business activities of a company. Sometimes condition of the assets is less reck so it affected its performance. The problems will appear as the tool is not reck, such as operational support will be hampered, and complaints from the customers. To solve the problems, the asset condition monitoring should be done by doing the inventory. Inventory assets is the ability to record assets, it is expected that fixed asset can be monitored the check-out/check-in process from the report by building an inventory system applications. By using that application system can always monitor and making decisions regarding fixed assets.Keyword:Inventory Applications, Fixed Asset.